Variations in coping stages for individuals with chronic kidney disease: Results from an exploratory study with patient navigators. (July 2016) - Marlow, Nicole M; Simpson, Kit N; Kazley, Abby S; Balliet, Wendy E; Chavin, Kenneth D; Baliga, Prabhakar K
Using a cross-sectional design, we examined coping stages (Kübler-Ross) among patients with end-stage renal disease at nephrology practices incorporating professional social workers as patient navigators, providing person-centered education and support ( N  = 420). We evaluated associations with behavioral counseling constructs ( assess–advise–agree–assist–arrange ). Coping stages comprised denial = 35.24 percent, acceptance = 24.05 percent, depression = 21.43 percent, bargaining = 12.86 percent, and anger = 6.43 percent. Compared to denial, other coping stages showed increased odds ratios for transplant referral agreement, transplant referral evaluations, understanding treatments, understanding donation procedures, plans to recruit donors, active donor recruitment, and potential living donor(s). Assessment of coping stages, and strategies to influence these, may be key factors in guiding patients to living donor kidney transplantation.